(untitled) (Journal of Tourism & Adventure, 2022)
The purpose of this article was to present awareness of extreme and adventure tourism among Polish people. A diagnostic survey was performed in order to determine the actual state of understanding of leisure activities and preferences of the people regarding adventure tourism using online social networking sites like Facebook in July 2021. A total of 1080 Polish respondents participated in the study, and the data were analysed descriptively. In this study, we found that leisure tourism is mostly practiced (41%) among the respondents, and the extreme and adventure tourism market share is 14%. Around 40% of respondents said they never practiced adventure tourism, and 26% said they hardly practice once a year. This demands additional efforts to increase the market share for extreme and adventure tourism. Thus, tourism entrepreneurs and policymakers can promote extreme and adventure tourism in the country, focusing on young people. Similarly, 31% said adventure and extreme tourism are dangerous. This means people must first overcome their psychological fear of participating in such activities. Thus, to encourage people in adventure and extreme tourism, the tourists’ fears should be removed and psychologically motivated. Then, ensuring safety measures, short training, and awareness campaigns focusing on the young increases their participation in adventure and extreme tourism. The safety measures and positive psychology in younger people increase the adventure and extreme tourism market.